The effects of soybean hulls on nursery pig growth performance - Goehring, D.L.; Tokach, Michael D.; DeRouchey, Joel M.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Two experiments were conducted to evaluate the effects of soybean hulls on growth performance of nursery pigs. In both experiments, pens of pigs were balanced by initial BW and randomly allotted to 1 of 5 dietary treatments with 6 replications per treatment. In Exp. 1, a total of 210 nursery pigs (PIC, 337 × 1050, initially 14.7 lb and 28 d of age) were used in a 34-d experiment. Diets contained increasing amounts of soybean hulls (0, 5, 10, 15, and 20%) and were not balanced for energy. Overall (d 0 to 34), pigs fed increasing soybean hulls had decreased ADG (linear, P < 0.01) and poorer F/G (linear, P < 0.001), with no change in ADFI (P > 0.23). Despite the linear response, the greatest decreases in pig performance were observed as soybean hulls were added at 10% or greater of the diet; those fed only 5% of the diet were similar to control pigs.
Keywords: Swine; NE; Nursery pig; Soybean hulls